Information Quality and Voluntary Disclosure - Penno, Mark C. (The Accounting Review, 1997)
[This paper examines the voluntary disclosure of nonproprietary information using the model of uncertain information endowment developed by Dye (1985) and Farrell (1986), and extended by Jung and Kwon (1988). The paper focuses on a broad family of functions relating the probability of information acquisition to ex post information quality. The paper shows that for each function there is some region that displays a negative relation between ex ante information quality and the frequency of disclosure. In addition, a sub-family of functions is identified for which ex ante information quality and the frequency of disclosure are negatively related everywhere. These results indicate that the economic intuition that higher informational asymmetry is accompanied by more voluntary disclosure is not generally true.]